The social meaning potential of loanwords: Empirical explorations of lexical borrowing as expression of (social) identity. (2019) - Zenner, Eline; Rosseel, Laura; Calude, Andreea Simona
Abstract: The use of loanwords is not merely a lexical act (filling a lexical gap in a given language, or using a shorter word in place of a longer expression) but also a socially meaningful one – a contextual expression of self, social identity and language regard. Recent lexical borrowing research has drawn attention to this social meaning potential of loanwords. What motivates language users to select a borrowed form over a receptor language equivalent, what is the (perceived) social meaning of this choice and how can we empirically address these questions? This special issue seeks to bring into debate the interface between speakers (the social dimension) and language (the linguistic dimension) with regard to lexical borrowing, and to probe how language regard and speaker identity influence and explain the use of loanwords. In a bid to better understand this complex interface, the special issue includes papers that explore a range of empirical methodologies drawn from different subfields of (socio)linguistics and closely related scientific domains (linguistic anthropology, conversation analysis, corpus linguistics, social psychology and psycholinguistics) and documents a variety of contact situations: English loans into French and Finnish, Māori loanwords into New Zealand English, German loans into Dutch. Together, the different perspectives presented in this issue help advance our understanding of the relationship between lexical change on the one hand, and language regard and (social) identity on the other hand. Highlights: This SI emphasizes the broad spectrum of social meanings indexed by lexical borrowing. This SI presents explorations of the topic of borrowing and identity from four different subfields of linguistics. This SI taps into four diverse contact situations. This SI opens up promising avenues for future research on the social meaning of lexical borrowing.